2015
DOI: 10.5056/jnm14077
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Ileus Following Orthopedic Surgery: The Role of Chronic Constipation

Abstract: Background/Aims Distinction is vague between severe constipation and postoperative ileus (POI) in terms of pathogenesis, clinical features, and treatment options. However, no data are available regarding their associations. Methods After retrospective review of data from patients who underwent orthopedic surgery during the first 6 months of 2011, a total of 612 patients were included. Severe constipation was defined as symptoms of constipation requiring treatment using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 20 publications
0
25
1
1
Order By: Relevance
“…Various factors, such as constipation, influence the time to bowel motility recovery, which leads to a possible misinterpretation of these factors as risk factors for POI [21]. As such, we believe that a classification of POI should be based on consequences rather than delay.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors, such as constipation, influence the time to bowel motility recovery, which leads to a possible misinterpretation of these factors as risk factors for POI [21]. As such, we believe that a classification of POI should be based on consequences rather than delay.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have focused on the risk factors for POI following scoliosis surgery. Most have reported the incidence of POI following spine surgery, which ranges from 0.6% to 16.7% [8][9][10][11] . The present study is the first to identify the incidence of and risk factors for POI after scoliosis surgery, and it revealed two important findings.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have evaluated the risk factors for POI following spine surgery. Such risk factors include a low body mass index, general anesthesia, gastroesophageal reflux disease, intraoperative administration of >2 L/day of crystalloid solutions, and severe constipation 9,10,12,13) . In the present study, the presence of NMS was identified as the main risk factor for POI following scoliosis surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that higher performance status is associated with more severe constipation in patients receiving opioid analgesic agents . Moreover, surgical operation often causes constipation, which becomes a risk for postoperative ileus …”
Section: Methodsmentioning
confidence: 99%
“…[15] Moreover, surgical operation often causes constipation, which becomes a risk for postoperative ileus. [16] This study was conducted according to the guidelines for human studies determined by the Ethical Committee of Gifu University Graduate School of Medicine and the Government of Japan, and was approved by the Medical Review Board of Gifu University Graduate School of Medicine (approval no. 28-87).…”
Section: Patientsmentioning
confidence: 99%